Penerapan Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) Dibantu Dengan Media Flashcard Untuk Meningkatkan Kemampuan Pemahaman Bacaan Siswa Disleksia Di Sekolah Dasar Yang Menyelenggarakan Pendidikan Inklusi - Agustin, Ina; Wardhono, Agus (Balai Diklat Keagamaan Surabaya, 2024)
This study intends to describe the Cooperative Integrated Reading Composition (CIRC) learning model's deployment with the use of Flashcard media and the improvement in dyslexic students' reading comprehension skills following the use of the CIRC model with Flashcard media. Research of this kind is referred to as classroom action research. This study's focus was on one student with special needs, namely dyslexia in class VI. The research site is at SDN Banjarworo II, Bangilan District, Tuban Regency. This study was conducted in two cycles, with each cycle consisting of one meeting. This research is class action research using a qualitative and qualified approach. The stages or steps carried out are (1) the planning stage, (2) the implementation stage, (3) the observation stage, and (4) the reflection stage. Data collection techniques use interview techniques, observations, tests, and documentation. Research instruments are interview sheets, observation sheets, and test sheets. Research results: At the stage of implementing the application of the CIRC model assisted by flashcard media, students pay attention to text and reading and make initial predictions. With the assistance of teachers, dyslexic students work in groups and practice doing presentations and class discussions, then do the reading comprehension ability test questions. In cycle 1, the assessment of teacher activities in implementing the CIRC learning model assisted by flashcard media was 80% with the criteria